Determination of cardiovascular risk level in spanish telephone operators: associated variables - López-González, Ángel A. (2021)
Introduction. Cardiovascular pathologies are the first cause of morbidity in Spain. The risk factors that influence their appearance and evolution include socioeconomic and labor aspects. The objective was to determine the level of cardiovascular risk in telephone operators. Material and methods. Retrospective and cross-sectional study in 1215 Spanish teleoperators in the period January 2017 and December 2017 in which different parameters related to cardiovascular risk are valued (overweight-obesity scales, cardiovascular risk scales, atherogenic indices, fatty liver risk scales and metabolic syndrome among others) and the influence on them of variables such as age, sex and tobacco use. The study was approved by the Clinical Research Ethics Committee of the Balearic Islands Health Area. Results. We highlight the high prevalence of high blood pressure in males (23.94%) obesity with BMI (20%), Hypercholesterolemia (27.89%) and high risk of fatty liver (23.36%). Age is the variable that shows the greatest influence on the cardiovascular risk factors analyzed. Conclusions. Although the average age of the sample is low (35.26 years in women and 33.61 years in men) a high prevalence of hypertension, obesity with different models, metabolic syndrome, moderate and high score and REGICOR values as well as high risk of fatty liver especially in men is observed.